PENILAIAN PORTOFOLIO BERBASIS GAYA BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INDONESIA SEBAGAI IMPLEMENTASI PENILAIAN KURIKULUM 2013 - Wikanengsih, Wikanengsih (Universitas Pendidikan Indonesia, 2014)
Curriculum 2013 has been implemented by the government at every level of school though gradually. This implementation requires educational practitioners particularly teachers to master a variety of learning support tools. This paper aims to examine and review the learning tools needed by a particular device for Curriculum 2013 assessment. Assessment as mandated by Curriculum 2013 is a competency-based assessment to measure attitudes, skills, and knowledge based on the process and learning outcomes. Incorporating an assessment of the process and learning outcomes, portfolio is the main instrument in the assessment. The portfolio that is commonly used nowadays has not addressed students’ characteristics and their learning styles. Review of the literature students’ learning styles-based protofolio including visual, auditory and kinesthetic styles